Inventarisasi Jenis-Jenis Ikan Cyprinidae di Sungai Batang Nareh, Kabupaten Padang Pariaman. - Mida Yulia Murni; - Dahelmi; Dewi Imelda Roesma (Universitas Andalas, 2014)
Species Inventory of the Cyprinid fishes at Batang Nareh River, Padang Pariaman using descriptive method was conducted from January to March 2013. Seven species of Cyprinid that belonging to five genera and 253 individuals were collected from three stasiun at Batang Nareh River. The species were Tor tambra CV, T. tambroides Blkr, Rasbora reticulata M. web & de Bfrt, R. laterastriata Blkr, Lobocheilos falcifer CV, Osteochilus hasseltii Blkr, and Puntius binotatus CV. Tor tambra and T. tambroides were reported as high economic value species for local people.Keywords: Inventory, Cyprinid, Batang Nareh River.